Lenalidomide in relapsed adult T-cell leukaemia-lymphoma or peripheral T-cell lymphoma (ATLL-001): a phase 1, multicentre, dose-escalation study. Issue 3 (March 2016) - Ogura, Michinori; Imaizumi, Yoshitaka; Uike, Naokuni; Asou, Norio; Utsunomiya, Atae; Uchida, Toshiki; Aoki, Tomohiro; Tsukasaki, Kunihiro; Taguchi, Jun; Choi, Ilseung; Maruyama, Dai; Nosaka, Kisato; et al.
Summary: Background: Patients with adult T-cell leukaemia-lymphoma have few treatment options after relapse and poor survival outcomes with current therapies. We aimed to determine the maximum tolerated dose of lenalidomide, an oral immunomodulator, in Japanese patients with relapsed adult T-cell leukaemia-lymphoma and other peripheral T-cell lymphomas. Methods: In this phase 1 study, we enrolled patients aged 20 years or older with Eastern Cooperative Oncology Group performance status 0–2, documented diagnosis of aggressive adult T-cell leukaemia-lymphoma or other peripheral T-cell lymphoma subtypes, and at least one previous antilymphoma therapy. Patients were sequentially assigned to lenalidomide 25 mg/day, days 1–21 of a 28-day cycle (cohort 1), 25 mg/day continuously (cohort 2), and 35 mg/day continuously (cohort 3) in a 3 + 3 design. The primary study endpoint was to identify the maximum tolerated dose of lenalidomide. Analyses were performed per protocol for efficacy and in the intent-to-treat patient population for safety. This completed trial is registered withClinicalTrials.gov, numberNCT01169298 . Findings: We enrolled 14 patients from six centres in Japan. Of 13 assessable patients (nine with adult T-cell leukaemia-lymphoma, four with other peripheral T-cell lymphomas) receiving lenalidomide, dose-limiting toxic effects were reported in three patients during cycle 1 (one grade 4 thrombocytopenia [cohort 2], one grade 3 QT prolongation on electrocardiogram [cohort 3], and one grade 3 fatigue and grade 4 thrombocytopenia [cohort 3]). The maximum tolerated dose was identified as lenalidomide 25 mg/day given continuously. The most common grade 3 or worse adverse events were neutropenia (eight [62%] patients), lymphopenia (seven [54%] patients), and thrombocytopenia (four [31%] patients); myelosuppression was similar in each cohort. Serious adverse events occurred in eight (62%) patients; thrombocytopenia, which occurred in three (23%) patients, was the only serious adverse event reported in more than one patient. Interpretation: We were able to determine the dose and schedule for lenalidomide treatment in previously treated patients with aggressive, adult T-cell leukaemia-lymphoma. This dose will be used in a subsequent phase 2 study. Funding: Celgene Corporation.